UP-TO-DATE DIET – WELL BALANCED NUTRITION - SPORT ACTIVITY (OPTIMIZAATION OF BODY MASS IN THE XXI CENTURY) - Pal Tolnay; Andras S. Szabo; Anna Kacsandi (Sport Scientific And Practical Aspects, 2025)
The paper deals with topics of up-to-date, with sport motion combined diet, helping in keeping the health, as well. In the last decades a lot of information were distributed concerning several viewpoints of bodyweight reduction and optimation. How should we know that it is useful and not unhealthy? A suitable Nutrition software (AOPNEI, Analysing and Optimation Program for Nourishment and Energy Intake) – developed at the Department of Food Chemistry and Nutrition of the Faculty of Food Science – can help.